The Role of Regional Language Short Films in Preserving Local Culture: A Case Study of Early Engagement on the Ponca Temor YouTube Channel: Peran Film Pendek Berbahasa Daerah dalam Pelestarian Budaya Lokal: Studi Kasus Film Pertunangan Dini pada Kanal YouTube Ponca Temor - syarful anam; senyum Sadhana (Jurnal Pendidikan Sendratasik, 2025)
The rapid expansion of digital media has created new opportunities for preserving local cultures, particularly through audiovisual content produced in regional languages. In Indonesia, the declining use of regional languages among younger generations has raised concerns regarding the sustainability of local cultural identity. This study investigates the role of regional-language short films in preserving local culture through a case study of Pertunangan Dini, a Madurese-language short film published on the Ponca Temor YouTube channel. Employing a qualitative case study approach, the research collected data through in-depth interviews with the film's production team and audience members, complemented by observation and document analysis. The analysis was informed by Pierre Bourdieu's Cultural Capital Theory, Henry Jenkins' Convergence Culture Theory, and Stuart Hall's Reception Theory. The findings demonstrate that the film functions as more than an entertainment product; it serves as a digital medium for transmitting the Madurese language, social values, customs, and collective cultural identity. The integration of the Madurese language with culturally embedded narratives enables audiences to recognize, appreciate, and reinterpret local traditions within a contemporary digital environment. Audience responses further reveal dominant, negotiated, and oppositional readings, indicating varying levels of cultural interpretation while maintaining the film's significance as a vehicle for cultural engagement. Moreover, YouTube facilitates wider accessibility and intergenerational dissemination, enhancing the visibility of regional culture beyond its geographical origin. The study concludes that regional-language short films constitute an effective strategy for strengthening cultural awareness and supporting the sustainability of local cultural heritage in the digital era. These findings contribute to broader discussions on digital media, regional-language revitalization, and community-based cultural preservation.